Perceived Social Support in Individuals With Diabetic Foot Ulcers: A Cross-sectional Survey - Laopoulou, Fotini; Kelesi, Martha; Fasoi, Georgia; Vasilopoulos, Georgios; Polikandrioti, Maria (Journal of wound, ostomy, and continence nursing, 2020)
Explore levels of perceived social support and the associated factors among patients with diabetic foot ulcers (DFUs). Cross-sectional survey. Outpatients (n = 140) with DFUs attending a diabetic clinic affiliated with a public hospital in Athens, Greece, for wound care and follow-up visits after healing. Data collection included demographic, clinical, self-report, and perceived social support, measured with the Multidimensional Scale of Perceived Social Support (MSPSS), during one-on-one interviews at the post-healing follow-up visit. For perceived social support, 50% of patients (average age 70 years) scored above 24, 24, and 18 (median) on the MSPSS in the categories of receiving support from significant other, family, and friends, respectively, suggesting high levels of perceived social support. Other statistically significant associations were observed for perceived social support from significant other, family, and friends and marital status (P = .001, P = .001, and P = .004, respectively), patients level of information about their health (P =.002, P =.001, and P =.001, respectively), family level of information (P = .001, P = .001, and P = .004, respectively), and how closely they followed period foot checks (P = .001, P = .002, and P = .011, respectively) and diet (P = .001, P = .001, and P = .001, respectively). Data from our study show that higher levels of perceived social support from significant others, family, and friends were linked to patients and others, being better informed about health status, and other self-care behaviors. Findings underscore the need for health care providers to recognize that social support is an important component of overall DFU management and may guide future interventions to determine which are most effective in enhancing socially supportive behaviors.